The Effectiveness of Principal Leadership Styles in Crisis Management - Purnomo, Eko Nurhaji; Supriyanto, Achmad; Mustiningsih; Dami, Zummy Anselmus (Pedagogika, 2023)
The research aimed to explore the types of effective principal leadership styles in crisis management at school. Data analysis using structural equation modeling. The results showed that transformational leadership had a strong positive effect on crisis management, charismatic leadership and transactional leadership had a positive but weak effect on crisis management. In contrast, entrepreneurial leadership had a negative but weak effect on crisis management.